Successful treatment of anorexia nervosa and alleviation of chronic Guillain Barré syndrome - Andreas Richterich; Thomas Stegemann; Anneke Aden (Mental Illness)
Eating disorders do not typically occur in conjunction with specific neurological disorders. Only very few cases of Guillain-Barré-Syndrome (GBS) associated with eating disorders have been reported. The objective of this paper is to describe and discuss a case of anorexia nervosa and concomittant chronic GBS. We report on a course of medical management for a 15 year old female patient, who presented with acute neurological syndrome (GBS) which was followed by the onset of a severe eating disorder. The patient was diagnosed to have two different entities, with the association between the two remaining unclear. The mainstay of management was focused on the eating disorder. Using an integrative psychiatric therapy a significant improvement of the eating disorder was achieved. The patient’s body weight was stabilised and the locomotor deficits improved. Though a significant somatic disorder was evident, it proved to be advantageous to primarily focus on the eating disorder, until it was under control. The possible correlations between the two distinct disorders are discussed.